Disagreeing with your professor: Exploring Chinese and American graduate students’ intercultural pragmatic strategies - Cai, Chencen; Ebsworth, Miriam Eisenstein; Ebsworth, Timothy John (Journal of International Students, 2024)
As American universities become increasingly diverse, students often encounter cross-cultural challenges. Chinese students represent one of the most substantial international U.S. student communities, with distinctive pragmatic norms and values. This study investigates Chinese international and American graduate students’ intercultural pragmatic strategies towards a face-threatening critical incident: expressing disagreement to a professor. Our mixed-methods design revealed quantitative and qualitative differences in participants’ strategies and judgments of alternatives, demonstrating distinctive underlying norms and values. Many American participants preferred to express different opinions in class, while Chinese students privileged more indirect options, though each group included participants with alternate preferences. Implications for cross-cultural communication and pedagogy are offered.